Qualitative Assessment of the Feasibility, Usability, and Acceptability of a Mobile Client Data App for Community-Based Maternal, Neonatal, and Child Care in Rural Ghana - LeFevre, Amnesty E.; Labrique, Alain B.; Romano, Karen; Gee, Lisa; Yang, Fan; Moorthy, Anitha; Jennings, Larissa; Rothstein, Jessica D.; Hutchful, David (International Journal of Telemedicine and Applications, 2016)
Mobile phone applications may enhance the delivery of critical health services and the accuracy of health service data. Yet, the opinions and experiences of frontline health workers on using mobile apps to track pregnant and recently delivered women are underreported. This evaluation qualitatively assessed the feasibility, usability, and acceptability of a mobile Client Data App for maternal, neonatal, and child client data management by community health nurses (CHNs) in rural Ghana. The mobile app enabled CHNs to enter, summarize, and query client data. It also sent visit reminders for clients and provided a mechanism to report level of care to district officers. Fourteen interviews and two focus groups with CHNs, midwives, and district health officers were conducted, coded, and thematically analyzed. Results indicated that the app was easily integrated into care, improved CHN productivity, and was acceptable due to its capacity to facilitate client follow-up, data reporting, and decision-making. However, the feasibility and usability of the app were hindered by high client volumes, staff shortages, and software and device challenges. Successful integration of mobile client data apps for frontline health workers in rural and resource-poor settings requires real-time monitoring, program investments, and targeted changes in human resources.